Bionic intrafascicular interfaces for recording and stimulating peripheral nerve fibers. Issue 1 (January 2018) - Jung, Ranu; Abbas, James J; Kuntaegowdanahalli, Sathyakumar; Thota, Anil K
The network of peripheral nerves presents extraordinary potential for modulating and/or monitoring the functioning of internal organs or the brain. The degree to which these pathways can be used to influence or observe neural activity patterns will depend greatly on the quality and specificity of the bionic interface. The anatomical organization, which consists of multiple nerve fibers clustered into fascicles within a nerve bundle, presents opportunities and challenges that may necessitate insertion of electrodes into individual fascicles to achieve the specificity that may be required for many clinical applications. This manuscript reviews the current state-of-the-art in bionic intrafascicular interfaces, presents specific concerns for stimulation and recording, describes key implementation considerations and discusses challenges for future designs of bionic intrafascicular interfaces.